If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5*(12-3)=5*e
We simplify the equation to the form, which is simple to understand
5*(12-3)=5*e
Reorder the terms in parentheses
+(+45)=+5e
Remove unnecessary parentheses
+45=+5e
We move all terms containing e to the left and all other terms to the right.
-5e=-45
We simplify left and right side of the equation.
-5e=-45
We divide both sides of the equation by -05 to get e.
e=9
| 15n=5.25 | | 6a+3+2a=19 | | 8y-16=8y+-16 | | 8=2(4j+1)-5j | | 5(6x+2)-8=30x+2 | | 5(y+9)=-2y-4 | | b=75 | | 9+8=-20 | | -6y+5=16 | | 8x+18=8x-2 | | a^2+ab-72b^2=0 | | 2(v-4)-8v=28 | | 3(t+8)+4=8(t+2)3 | | 14-x=-38 | | 46.50-15=5.25 | | 13x-4=-43 | | -4(-4+x)=54 | | 3-7(2-x)=5k+2(-2-4x) | | 35+2x=58 | | 8x-8=6x+28 | | 8a+3-5a-2a= | | (X-1)+5+x=12 | | 2g+4=24 | | 5.7+6.6= | | (7x+15)=(10-9) | | 36x=8-14p | | 3=17-7n | | 14=4(7-8p)-6(4p-7) | | 250+14(h)=22(h) | | -y+3-3=-6 | | 5(2x-3)=7x+15 | | 11x-15=40 |